Qualitative focus group discussions exploring PrEP method and service delivery preferences among female sex workers and their managers in four Zambian provinces - Holly M Burke; Emily Evens; Tendai Munthali; Featherstone Mangunje; Mercy L Kotaka; Bupe Musonda; Musonda Musonda; Catherine S Todd (BMJ Public Health)
Objectives To describe the experiences of oral HIV pre-exposure prophylaxis (PrEP) use, preferences comparing oral PrEP to future long-acting PrEP products (the dapivirine vaginal ring (PrEP ring) and injectable cabotegravir (CAB PrEP)), and service provision preferences among female sex workers (FSWs) and their managers.Methods Qualitative formative focus group discussions were conducted in two urban (Copperbelt, Lusaka) and two rural (Central, Luapula) provinces in Zambia. Consenting participants included 43 FSWs and 36 sex work managers. Eligible participants self-identified as FSWs or sex work managers, were 18 years or older and spoke English, Nyanja or Bemba.Results FSWs had a median age of 28 years and 60% reported ever using oral PrEP. Among potential future HIV prevention options, most FSWs preferred longer acting PrEP methods, mainly CAB PrEP over the PrEP ring. This preference was consistent across provinces. Many FSWs had personal oral PrEP experience and appreciated the high effectiveness but conveyed that the realities of daily use, including pill visibility, and attributed side effects did not meet their needs. FSWs and managers also identified frequent stigma and misinformation-related barriers to PrEP access and use at community and facility levels. Most FSWs and managers agreed that informing non-paying or long-term partners of PrEP use was acceptable. Participants offered recommendations for greater sensitisation and peer-led services or service extension through trusted figures in the community.Conclusions Zambian FSWs and their managers preferred longer acting PrEP methods, particularly CAB PrEP, as part of comprehensive HIV prevention method choice, with little difference between provinces. PrEP programming led by FSW peers, managers or other trusted figures was recommended to address misinformation, sensitise partners and potentially deliver services to circumvent perceived stigma at health facilities.